Brain network changes in adult victims of violence - Shymanskaya, Aliaksandra; Kohn, Nils; Habel, Ute; Wagels, Lisa (Frontiers in Psychiatry, 2023)
Introduction Stressful experiences such as violence can affect mental health severely. The effects are associated with changes in structural and functional brain networks. The current study aimed to investigate brain network changes in four large-scale brain networks, the default mode network, the salience network, the fronto-parietal network, and the dorsal attention network in self-identified victims of violence and controls who did not identify themselves as victims. Materials and methods The control group (n = 32) was matched to the victim group (n = 32) by age, gender, and primary psychiatric disorder. Sparse inverse covariance maps were derived from functional resting-state measurements and from T1 weighted structural data for both groups. Results Our data underlined that mostly the salience network was affected in the sample of self-identified victims. In self-identified victims with a current psychiatric diagnosis, the dorsal attention network was mostly affected underlining the potential role of psychopathological alterations on attention-related processes. Conclusion The results showed that individuals who identify themselves as victim demonstrated significant differences in all considered networks, both within- and between-network.